Oxygen-absorbing resin composition, oxygen-absorbing film, oxygen-absorbing multilayer film and cover material

By using an oxygen-absorbing resin composition composed of a specific proportion of polyolefin, iron powder, titanium oxide and calcium oxide in the packaging material, the problem of deterioration of appearance and odor in the packaging material is solved, and the oxygen-absorbing, light-shielding and odor suppression performance is improved.

CN116457411BActive Publication Date: 2025-04-18MITSUBISHI GAS CHEM CO INC
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202180078606.5
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Priority Date
2020-11-30
Filing Date
2021-11-15
Publication Date
2025-04-18
Estimated Expiration
2041-11-15

AI Technical Summary

Technical Problem

When the iron powder used in existing packaging materials is used as an oxygen absorber, it is easy to cause a poor appearance and cannot be printed clearly. It may produce odor when heated, affecting the use effect of the packaging materials.

Method used

An oxygen-absorbing resin composition composed of polyolefin, iron powder, titanium oxide and calcium oxide are used to maintain oxygen absorption properties and improve light shielding properties and odor suppression properties by adjusting the proportion of these components, for example, the content of iron powder is 10 to 50 mass%, the mass ratio of titanium oxide to iron powder is 0.1 to 0.5, and the mass ratio of calcium oxide to iron powder is 0.1 to 0.5.

Benefits of technology

It realizes packaging materials with excellent oxygen absorption, light shielding and odor suppression performance, solves the problem of iron powder in packaging materials, and improves the appearance and functional performance of the material.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0004241666840000221
    Figure BDA0004241666840000221
Patent Text Reader

Abstract

An oxygen-absorbing resin composition contains polyolefin, iron powder, titanium oxide and calcium oxide, wherein the content of the iron powder in the oxygen-absorbing resin composition is 10 to 50% by mass, the mass ratio of titanium oxide to iron powder [titanium oxide / iron powder] is 0.1 to 0.5, and the mass ratio of calcium oxide to iron powder [calcium oxide / iron powder] is 0.1 to 0.5.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to an oxygen-absorbing resin composition, an oxygen-absorbing film, an oxygen-absorbing multilayer film and a cover material. Background Art

[0002] In the past, cans were used as packaging materials for foods with a long shelf life of years. When cans are used to store foods, they have high gas barrier properties against oxygen, water vapor, etc., but they have the following problems: they cannot be heated in an electric oven; when the filled foods are placed on a plate, it is difficult to take out the foods; they cannot be stacked when discarded after use, the volume of discarded cans is large, and the adaptability to disposal is poor.

[0003] Therefore, studies have been conducted on the application of plastic containers to packaging containers that aim to have a long shelf life as described above.

[0004] As one example, a packaging container has been developed that includes a multilayer material having a deoxidizing resin layer mixed with a deoxidizer composition, thereby improving the gas barrier properties of the container and imparting a deoxidizing function to the container itself.

[0005] For example, Patent Document 1 discloses that a gas barrier layer, an oxygen absorbing layer formed of an oxygen absorbing resin composition prepared by blending an iron-based oxygen absorber with a thermoplastic resin, and a heat seal layer formed of a heat seal resin are sequentially provided in order to achieve good cutting properties after sealing and good appearance after opening for use in a gas barrier molded container, wherein the density of the heat seal resin is 0.930 g / cm 3 The above deoxidizing cover material.

[0006] Prior art literature

[0007] Patent Literature

[0008] Patent Document 1: Japanese Patent Application Publication No. 2004-315035 Summary of the invention

[0009] Problem that the invention aims to solve

[0010] As listed in Patent Document 1, iron powder is widely used as an oxygen absorbent in packaging materials having deoxidizing properties. However, if a large amount of iron powder is mixed with a resin to impart oxygen absorbing properties, the appearance may be deteriorated or the printing may not be clear. In addition, when the iron powder is mixed with the resin or when the package is heated, an odor may be generated.

[0011] Therefore, there is a demand for a resin material and a resin film which can be used as a packaging material having excellent light-shielding properties and odor-suppressing performance while maintaining the excellent oxygen-absorbing properties of iron powder.

[0012] An object of the present invention is to provide an oxygen-absorbing resin composition and an oxygen-absorbing film which are excellent in oxygen absorbing property and also excellent in light-shielding property and odor-suppressing performance.

[0013] Solutions for solving problems

[0014] The present invention is as follows.

[0015] <1> An oxygen-absorbing resin composition contains polyolefin, iron powder, titanium oxide and calcium oxide, wherein the content of the iron powder in the oxygen-absorbing resin composition is 10 to 50% by mass, the mass ratio of titanium oxide to iron powder [titanium oxide / iron powder] is 0.1 to 0.5, and the mass ratio of calcium oxide to iron powder [calcium oxide / iron powder] is 0.1 to 0.5.

[0016] <2> According to the above <1> In the oxygen-absorbing resin composition, the mass ratio of titanium oxide to iron powder [titanium oxide / iron powder] is 0.15 to 0.5.

[0017] <3> According to the above <1> or <2> The oxygen-absorbing resin composition has a mass ratio of calcium oxide to titanium oxide [calcium oxide / titanium oxide] of 0.6 to 1.5.

[0018] <4> According to the above <1> ~ <3> The oxygen-absorbing resin composition according to any one of the preceding claims, wherein the content of titanium oxide in the oxygen-absorbing resin composition is 1 to 15% by mass.

[0019] <5> According to the above <1> ~ <4> The oxygen-absorbing resin composition according to any one of the preceding claims, wherein the content of calcium oxide in the oxygen-absorbing resin composition is 1 to 15% by mass.

[0020] <6> An oxygen-absorbing film, which is made of the above <1> ~ <5> The invention is formed from the oxygen-absorbing resin composition described in any one of the preceding claims.

[0021] <7> An oxygen-absorbing multilayer film comprising the above <6> The oxygen absorbing film is used as the oxygen absorbing layer.

[0022] <8> According to the above <7> The oxygen-absorbing multilayer film has a multilayer structure in which a layer having polyolefin as a main component, an oxygen-absorbing layer, and a gas-barrier layer are sequentially stacked.

[0023] <9> According to the above <7> or <8> The oxygen-absorbing multilayer film has an oxygen-absorbing layer with a thickness of 10 to 200 μm.

[0024] <10> According to the above <8> or <9> The oxygen-absorbing multilayer film, wherein the gas barrier layer is a metal thin film, an inorganic vapor-deposited film, or a layer containing at least one selected from ethylene vinyl alcohol copolymer and a polyamide resin.

[0025] <11>The oxygen-absorbing multilayer film according to any one of <7> to <10> above, wherein titanium oxide is contained only in the oxygen-absorbing layer.

[0026] <12>A lid material comprising the oxygen-absorbing multilayer film according to any one of <7> to <11> above.

[0027] It should be noted that in this specification, "containing as a main component" means containing preferably 90% by mass or more, more preferably 95% by mass or more, and further preferably 98% by mass or more, and other components may be contained within the range that does not hinder the effects of the present invention.

[0028] Effects of the Invention

[0029] The oxygen-absorbing resin composition of the present invention has excellent oxygen-absorbing properties, and furthermore, excellent light-shielding properties and odor-inhibiting properties. Detailed Embodiments

[0030] An embodiment of the present invention will be described below. The content of the present invention is not limited by the embodiments described below.

[0031] It should be noted that in this specification, the term "A to B" for the description of numerical values means "A or more and B or less" (when A < B) or "A or less and B or more" (when A > B). In addition, in the present invention, a combination of preferred modes is a more preferred mode.

[0032] [Oxygen-Absorbing Resin Composition]

[0033] The oxygen-absorbing resin composition of the present invention contains polyolefin, iron powder, titanium oxide, and calcium oxide. The content of iron powder in the oxygen-absorbing resin composition is 10 to 50% by mass, the mass ratio of titanium oxide to iron powder [titanium oxide / iron powder] is 0.1 to 0.5, and the mass ratio of calcium oxide to iron powder [calcium oxide / iron powder] is 0.1 to 0.5.

[0034] The oxygen-absorbing resin composition of the present invention has excellent oxygen-absorbing properties due to the aforementioned technical features, and furthermore, excellent light-shielding properties and odor-inhibiting properties.

[0035] Iron powder has a high oxygen-absorbing ability, but it is easily colored black or brown, and it also participates in the decomposition of the resin, etc. Therefore, when used in packaging materials such as lid materials, it causes a decrease in printing adaptability and odor generation. Sometimes, titanium oxide is added to improve printing adaptability and improve the appearance, or calcium oxide is added to inhibit odors, but titanium oxide and calcium oxide have an adverse effect on oxygen-absorbing properties, etc. In the present invention, it has been found that when they are contained in polyolefin at a specific ratio, the oxygen-absorbing properties can be maintained or further improved, and the light-shielding properties and odor-inhibiting properties can be improved. As described later, an oxygen-absorbing resin composition useful as a material for packaging materials, particularly lid materials, can be obtained.

[0036] <Polyolefin>

[0037] The polyolefin used in the oxygen-absorbing resin composition of the present invention includes polyolefins such as polyethylene, polypropylene, polybutene, polybutadiene, polymethylpentene, ethylene-propylene copolymer, propylene-ethylene block copolymer, etc.; polyolefin copolymers such as ethylene-vinyl acetate copolymer, ethylene-acrylic acid copolymer, ethylene-acrylic acid ester copolymer, ethylene-methacrylic acid copolymer, ethylene-methacrylic acid ester copolymer, etc.; the aforementioned polyolefins or the aforementioned polyolefin copolymers and silicone resin graft polymers, etc. Among them, polyolefins are preferred, at least one selected from the group consisting of polyethylene, polypropylene and ethylene-propylene copolymers is more preferred, at least one selected from the group consisting of polyethylene and polypropylene is further preferred, and polyethylene is further preferred. Among polyethylenes, low-density polyethylene is preferred from the viewpoint of gas permeability, and linear low-density polyethylene is more preferred.

[0038] The above-mentioned polyolefins can be used alone or in combination of two or more.

[0039] <Iron Fan>

[0040] The iron powder used in the oxygen-absorbing resin composition of the present invention is not particularly limited as long as it can be dispersed in the resin and can produce a deoxidation reaction, and iron powder generally used as a deoxidizer can be used. Specific examples of iron powder include reduced iron powder, sponge iron powder, spray iron powder, iron grinding powder, electrolytic iron powder, pulverized iron, etc. In addition, iron powder with a small content of oxygen and silicon as impurities is preferred, and iron powder with a metallic iron content of 95% by mass or more is particularly preferred.

[0041] The content of the iron powder in the oxygen absorbing resin composition is 10 to 50% by mass, preferably 10 to 40% by mass, more preferably 10 to 30% by mass, further preferably 15 to 25% by mass, and further preferably 18 to 25% by mass. Within this range, good deoxidation performance can be exhibited without adversely affecting the appearance.

[0042] From the viewpoint of deoxidation performance, the iron powder is preferably used in the form of a deoxidizer composition comprising the iron powder and a metal halide. The metal halide catalytically acts on the oxygen absorption reaction of metallic iron to improve the oxygen absorption performance.

[0043] Preferred specific examples of the metal in the metal halide include at least one selected from the group consisting of alkali metals, alkaline earth metals, copper, zinc, aluminum, tin, iron, cobalt and nickel. Lithium, potassium, sodium, magnesium, calcium, barium and iron are particularly preferred. In addition, preferred specific examples of the halide include chloride, bromide and iodide, and chloride is particularly preferred.

[0044] The amount of the metal halide is preferably 0.1 to 20 parts by mass relative to 100 parts by mass of the iron powder. It is preferred that the total amount of the metal halide is substantially attached to the iron powder and there is almost no free metal halide in the deoxidizer composition. When the metal halide works effectively, it is more preferably 0.1 to 5 parts by mass relative to 100 parts by mass of the iron powder.

[0045] In the present invention, the iron powder is preferably used in the form of a deoxidizer composition in which a metal halide is attached to the iron powder, and more preferably a deoxidizer composition in which the surface of the iron powder is covered with the metal halide.

[0046] The above-mentioned metal halide is preferably added by a method that is not easily separated from metallic iron, for example, preferably a method of burying fine metal halide particles on the surface of iron powder by crushing and mixing using a ball mill, a fast mill, etc.; a method of attaching fine metal halide particles to the surface of iron powder using a binder; a method of attaching fine metal halide particles to the surface of iron powder by mixing and drying an aqueous metal halide solution with iron powder. Among them, the deoxidizer composition is preferably produced by mixing an aqueous metal halide solution with iron powder and then drying to remove moisture.

[0047] The deoxidizer composition preferably has a reduced water content, and the water content of the deoxidizer composition is preferably 0.2 mass % or less, more preferably 0.1 mass % or less. When the deoxidizer composition is used as the resin composition of the present invention, it obtains water and exhibits an oxygen absorbing function.

[0048] The average particle size of the iron powder is 1 μm or more and less than 100 μm, preferably 1 μm or more and less than 80 μm, more preferably 1 μm or more and less than 50 μm, and further preferably 1 μm or more and less than 40 μm.

[0049] The maximum particle size of the iron powder is preferably 150 μm or less, more preferably 100 μm or less, further preferably 80 μm or less, and further preferably 70 μm or less.

[0050] If the particle size of the iron powder is within the above range, sufficient deoxidation can be achieved with a small amount of iron powder. In addition, since the iron powder has a small particle size and excellent deoxidation, even when the oxygen-absorbing resin composition is used in a multilayer film described later, the oxygen-absorbing layer containing the iron powder can be made thinner and the appearance is also excellent.

[0051] The average particle size and maximum particle size of the iron powder can be measured by a particle size measuring device such as a laser diffraction particle size distribution measuring device “LMS-2000e (trade name)” (manufactured by SEISHIN ENTERPRISE Co., Ltd.).

[0052] <Titanium oxide>

[0053] The titanium oxide used in the oxygen-absorbing resin composition of the present invention not only imparts light-shielding and concealing properties to the resin composition and the film, but also improves the appearance and coloring in white, thereby improving the printability.

[0054] Titanium oxide is not particularly limited, but is preferably white titanium dioxide (TiO 2 The crystal structure of titanium oxide is not particularly limited, and any of rutile type and anatase type can be used, and the rutile type structure is preferred.

[0055] From the viewpoint of improving affinity with the components constituting the oxygen-absorbing resin composition of the present invention and uniformly dispersing the titanium oxide, titanium oxide surface-treated with a silane coupling agent or the like may be used.

[0056] The average particle size of titanium oxide is preferably 0.01 to 10 μm, more preferably 0.1 to 8 μm, and further preferably 0.2 to 5 μm.

[0057] The average particle size of titanium oxide can be measured by a particle size measuring device such as a laser diffraction particle size distribution measuring device (same as above).

[0058] The content of titanium oxide in the oxygen absorbing resin composition is preferably 1 to 15% by mass, more preferably 2 to 10% by mass, and further preferably 4 to 7% by mass in the oxygen absorbing resin composition.

[0059] From the viewpoint of being uniformly dispersed in the resin composition of the present invention, titanium oxide is preferably used in the form of a masterbatch containing titanium oxide and a resin. As the resin contained in the masterbatch, any thermoplastic resin is sufficient, but in particular, from the viewpoint of compatibility with the aforementioned polyolefin constituting the resin composition of the present invention, polyolefin is preferably used. Examples include polyethylene represented by low-density polyethylene, medium-density polyethylene, high-density polyethylene, linear low-density polyethylene, etc., polypropylene represented by propylene homopolymers, ethylene-propylene block copolymers, ethylene-propylene random copolymers, etc., homopolymers of ethylene hydrocarbons having more than 2 carbon atoms, homopolymers of α-olefins having 3 to 20 carbon atoms, copolymers of α-olefins having 3 to 20 carbon atoms, copolymers of α-olefins having 3 to 20 carbon atoms and cyclic olefins, etc.

[0060] The content of titanium oxide in the masterbatch is preferably 30 to 90% by mass, more preferably 40 to 80% by mass, and still more preferably 50 to 70% by mass.

[0061] <Calcium oxide>

[0062] The calcium oxide used in the oxygen-absorbing resin composition of the present invention can reduce the odor generated during the production and use of the resin composition and film without affecting the oxygen absorbing property and light shielding property.

[0063] The average particle size of calcium oxide is preferably 0.1 to 20 μm, more preferably 1 to 10 μm.

[0064] The average particle size of calcium oxide can be measured by a particle size measuring device such as a laser diffraction particle size distribution measuring device (same as above).

[0065] The content of calcium oxide in the oxygen absorbing resin composition is preferably 0.5 to 15% by mass, more preferably 1 to 15% by mass, further preferably 1 to 10% by mass, further preferably 2 to 9% by mass, particularly preferably 5 to 8% by mass in the oxygen absorbing resin composition.

[0066] From the viewpoint of being uniformly dispersed in the resin composition of the present invention, calcium oxide is preferably used in the form of a masterbatch containing calcium oxide and a resin. As the resin contained in the masterbatch, any thermoplastic resin is sufficient, but in particular, from the viewpoint of compatibility with the aforementioned polyolefin constituting the resin composition of the present invention, polyolefin is preferably used. Examples include polyethylene represented by low-density polyethylene, medium-density polyethylene, high-density polyethylene, linear low-density polyethylene, etc., polypropylene represented by propylene homopolymers, ethylene-propylene block copolymers, ethylene-propylene random copolymers, etc., homopolymers of ethylene hydrocarbons having more than 2 carbon atoms, homopolymers of α-olefins having 3 to 20 carbon atoms, copolymers of α-olefins having 3 to 20 carbon atoms, copolymers of α-olefins having 3 to 20 carbon atoms and cyclic olefins, etc.

[0067] The content of calcium oxide in the masterbatch is preferably 35 to 90% by mass, more preferably 45 to 85% by mass, and still more preferably 55 to 75% by mass.

[0068] <Composition / production method / application etc. of oxygen-absorbing resin composition>

[0069] The oxygen-absorbing resin composition of the present invention contains the above-described polyolefin, iron powder, titanium oxide, and calcium oxide, and these are preferably contained in the following ratios.

[0070] The mass ratio of titanium oxide to iron powder [titanium oxide / iron powder] is 0.1 to 0.5, preferably 0.15 to 0.5, more preferably 0.15 to 0.4, and further preferably 0.2 to 0.3 from the viewpoint of oxygen absorption performance and light shielding properties.

[0071] The mass ratio of calcium oxide to iron powder [calcium oxide / iron powder] is 0.1 to 0.5, and from the viewpoint of oxygen absorption performance and odor suppression performance, preferably 0.1 to 0.45, more preferably 0.15 to 0.45, further preferably 0.2 to 0.4, further preferably 0.25 to 0.4, further preferably 0.25 to 0.35.

[0072] The mass ratio of calcium oxide to titanium oxide [calcium oxide / titanium oxide] is preferably 0.4 to 1.6, more preferably 0.6 to 1.5, and even more preferably 1.0 to 1.5.

[0073] The oxygen-absorbing resin composition of the present invention can be obtained by any production method, but is preferably obtained by melt-kneading the master batches described in the above-mentioned <titanium oxide> and <calcium oxide>, the above-mentioned iron powder and the above-mentioned polyolefin.

[0074] It should be noted that the iron powder is preferably used in the form of a deoxidizer composition containing the above-mentioned metal halide.

[0075] In order to uniformly disperse the components in the composition and easily adjust the concentration of the components according to the application, it is more preferred to melt-knead the masterbatches described in the above-mentioned <titanium oxide> and <calcium oxide>, the iron powder, and a part of the polyolefin to obtain an oxygen absorbing resin masterbatch, and then melt-knead the remaining part of the polyolefin according to the application to obtain an oxygen absorbing resin composition.

[0076] The content of the polyolefin in the oxygen-absorbing resin masterbatch is preferably 10 to 50 parts by mass, more preferably 15 to 40 parts by mass, and even more preferably 20 to 30 parts by mass, based on 100 parts by mass of all the polyolefins in the oxygen-absorbing resin composition of the present invention. The content of the polyolefin in the oxygen-absorbing resin masterbatch also includes the polyolefin contained in the masterbatch of titanium oxide and the masterbatch of calcium oxide.

[0077] The oxygen-absorbing resin composition is excellent in oxygen absorbing property and also excellent in light-shielding property and odor-suppressing performance, and therefore is suitable for use in packaging containers.

[0078] When used for packaging containers, the present resin composition may be directly formed into a film or the like and used as a packaging container, but is preferably used as a packaging container having a multilayer structure by forming a multilayer structure with other resins or resin compositions.

[0079] Examples of suitable packaging containers for the oxygen-absorbing resin composition of the present invention include pouches, container covers, trays, cups, laminated tube containers, bottles, and blister containers. Among them, pouches, container covers, and trays are preferred, and container covers are more preferred.

[0080] Among the above packaging containers, pouches, lids, laminated tubes, etc., films or multilayer films are preferably used, and oxygen-absorbing films or oxygen-absorbing multilayer films containing the oxygen-absorbing resin composition of the present invention are preferably used. Suitable oxygen-absorbing films and oxygen-absorbing multilayer films are described below.

[0081] In the above-mentioned packaging container, the tray is preferably an oxygen-absorbing multilayer tray with a multilayer structure, and the oxygen-absorbing multilayer tray preferably has a layer containing the first polyolefin as a main component, an oxygen-absorbing layer, a gas barrier layer, and a protective layer.

[0082] Each layer is preferably composed of the materials described in each of the items of <layer containing polyolefin as a main component>, <oxygen absorbing layer>, <gas barrier layer>, and <protective layer> in the oxygen absorbing multilayer film described later.

[0083] The packaging container using the oxygen-absorbing resin composition of the present invention is excellent in oxygen absorbing property and also excellent in light shielding property and odor suppressing performance, and therefore is suitable for packaging of various articles, and in particular, is suitable for packaging of foods.

[0084] Examples of the objects to be stored in the packaging container using the oxygen-absorbing resin composition of the present invention include beverages such as milk, dairy products, fruit juice, coffee, tea, and alcoholic beverages; liquid seasonings such as sauce, soy sauce, and dressing, and cooked foods such as soup, stew, curry, cooked foods for infants and nursing care; paste-like foods such as jam, mayonnaise, ketchup, and jelly; aquatic products such as tuna, fish, and shellfish; processed dairy products such as cheese and butter; processed livestock meat products such as meat, salami, sausage, and ham; vegetables such as carrots and potatoes; eggs; noodles; processed rice before cooking, cooked rice, rice porridge, and other processed rice products; powdered seasonings, powdered coffee, powdered milk for infants, powdered diet foods, dried vegetables, pancakes, and other dry foods; and the like.

[0085] [Oxygen absorbing film]

[0086] The oxygen-absorbing film of the present invention is formed from the above-mentioned oxygen-absorbing resin composition. That is, the oxygen-absorbing film of the present invention is formed from the oxygen-absorbing resin composition, and the oxygen-absorbing resin composition contains polyolefin, iron powder, titanium oxide and calcium oxide, the content of the iron powder in the oxygen-absorbing resin composition is 10 to 50% by mass, the mass ratio of titanium oxide to iron powder [titanium oxide / iron powder] is 0.1 to 0.5, and the mass ratio of calcium oxide to iron powder [calcium oxide / iron powder] is 0.1 to 0.5.

[0087] The above-mentioned components and ratios in the oxygen-absorbing film of the present invention are the same as those described in the above section of [oxygen-absorbing resin composition].

[0088] The thickness of the oxygen-absorbing film of the present invention is preferably 10 to 200 μm, more preferably 10 to 150 μm, further preferably 20 to 150 μm, further preferably 20 to 100 μm, further preferably 20 to 50 μm.

[0089] When the thickness of the oxygen absorbing layer is within the above range, the balance among oxygen absorbing property, light shielding property, and odor suppressing performance is excellent.

[0090] The oxygen-absorbing film of the present invention can be obtained by press molding, extrusion molding using an extruder and a T-die, calendar molding, etc. In addition, stretching treatment may be appropriately performed.

[0091] The oxygen-absorbing multilayer film described later contains the present oxygen-absorbing film as an oxygen-absorbing layer, and when the oxygen-absorbing layer of the multilayer film is formed, it can be formed simultaneously with other layers.

[0092] [Oxygen-absorbing multilayer film]

[0093] The oxygen-absorbing multilayer film of the present invention contains the above-mentioned oxygen-absorbing film as an oxygen-absorbing layer.

[0094] That is, the oxygen-absorbing multilayer film of the present invention contains an oxygen-absorbing film formed of an oxygen-absorbing resin composition as an oxygen-absorbing layer, wherein the oxygen-absorbing resin composition contains polyolefin, iron powder, titanium oxide and calcium oxide, the content of the iron powder in the oxygen-absorbing resin composition is 10 to 50% by mass, the mass ratio of titanium oxide to iron powder [titanium oxide / iron powder] is 0.1 to 0.5, and the mass ratio of calcium oxide to iron powder [calcium oxide / iron powder] is 0.1 to 0.5.

[0095] The oxygen-absorbing multilayer film of the present invention preferably has a multilayer structure in which a layer containing polyolefin as a main component, an oxygen-absorbing layer, and a gas barrier layer are sequentially laminated.

[0096] <Layer containing polyolefin as main component>

[0097] When the oxygen-absorbing multilayer film of the present invention is used for a packaging container or a lid, the layer containing polyolefin as a main component is preferably in contact with the space inside the container or the contents in the container.

[0098] The layer mainly composed of polyolefin plays the role of a barrier layer that prevents the contents in the container from directly contacting the adjacent oxygen absorbing layer, and also plays the role of allowing oxygen in the container to quickly and efficiently permeate so that the oxygen absorbing layer can fully exert its oxygen absorbing function.

[0099] The layer containing polyolefin as a main component contains polyolefin as a main component.

[0100] As polyolefins, polyolefins such as polyethylene, polypropylene, polybutene, polybutadiene, polymethylpentene, ethylene-propylene copolymer, propylene-ethylene block copolymer, etc. can be cited; polyolefin copolymers such as ethylene-vinyl acetate copolymer, ethylene-acrylic acid copolymer, ethylene-acrylate copolymer, ethylene-methacrylic acid copolymer, ethylene-methacrylate copolymer, etc.; the aforementioned polyolefins or the aforementioned polyolefin copolymers and silicone resin graft polymers, etc., among which polyolefins are preferred, at least one selected from the group consisting of polyethylene, polypropylene and ethylene-propylene copolymers is more preferred, at least one selected from the group consisting of polyethylene and polypropylene is further preferred, and polyethylene is further preferred. They can be used alone or in combination of two or more.

[0101] In addition, the polyolefin is preferably compatible with the oxygen absorbing resin composition used in the oxygen absorbing layer. By selecting mutually compatible resins, the layer mainly composed of the polyolefin and the resins of the oxygen absorbing layer can be coextruded and laminated.

[0102] For the layer with polyolefin as the main component, when the oxygen-absorbing multilayer film is used for a packaging container, it is mostly used as the innermost layer (the layer in contact with the inside of the packaging container) of the oxygen-absorbing multilayer film to play the role of a sealant layer, and a heat-sealable resin is preferably selected, but a heat-sealable layer may be further provided on the inner surface side. It should be noted that the resin constituting the innermost layer may be mixed with additives such as a colorant, a filler, an antistatic agent, and a stabilizer as required.

[0103] The layer with the polyolefin as the main component is required to play the role of a barrier between the contents in the container and the oxygen absorbing layer as described above, and to play the role of rapidly and effectively permeating oxygen in the container. Therefore, regardless of the presence or absence of other layers such as the aforementioned heat seal layer and the thickness of the layer itself, the oxygen permeability of the layer is preferably at least 100 mL / m 2 ·day·atm(23℃,100%RH)or more.

[0104] From the viewpoint of moldability and oxygen permeability, the thickness of the layer containing the present polyolefin as a main component is preferably 10 to 200 μm, more preferably 20 to 100 μm, further preferably 30 to 80 μm, further preferably 40 to 60 μm.

[0105] <Oxygen Absorption Layer>

[0106] The oxygen absorbing layer is the aforementioned oxygen absorbing film. That is, the oxygen absorbing layer is formed of an oxygen absorbing resin composition, the oxygen absorbing resin composition contains polyolefin, iron powder, titanium oxide and calcium oxide, the content of iron powder in the oxygen absorbing resin composition is 10 to 50% by mass, the mass ratio of titanium oxide to iron powder [titanium oxide / iron powder] is 0.1 to 0.5, and the mass ratio of calcium oxide to iron powder [calcium oxide / iron powder] is 0.1 to 0.5. Therefore, the oxygen absorbing layer is preferably the components and ratios described in the aforementioned [oxygen absorbing resin composition].

[0107] The oxygen absorbing layer contains titanium oxide as described above, and in the oxygen absorbing multilayer film of the present invention, titanium oxide is preferably contained only in the oxygen absorbing layer.

[0108] The thickness of the oxygen absorbing layer is preferably the same as that of the oxygen absorbing film, and is preferably 10 to 200 μm, more preferably 10 to 150 μm, further preferably 20 to 150 μm, further preferably 20 to 100 μm, further preferably 20 to 50 μm.

[0109] When the thickness of the oxygen absorbing layer is within the above range, the balance among oxygen absorbing property, light shielding property and odor suppressing performance is excellent.

[0110] <Gas barrier layer>

[0111] When the oxygen-absorbing multilayer film of the present invention is used for a packaging container or a cover material, the gas barrier layer plays a role in blocking oxygen entering from the outside.

[0112] The gas barrier layer may be provided as one layer or two or more layers in the oxygen-absorbing multilayer film as necessary. By providing two or more layers, the intrusion of oxygen from the outside can be more effectively suppressed.

[0113] The gas barrier layer is preferably a metal thin film, an inorganic vapor-deposited film, or a layer comprising at least one of a gas barrier resin selected from ethylene vinyl alcohol copolymer and a polyamide resin. In addition to the gas barrier properties, from the viewpoint of ease of molding and design, a layer comprising at least one of a selected from ethylene vinyl alcohol copolymer and a polyamide resin is more preferred, and a polyamide resin is further preferred.

[0114] Examples of the metal thin film include an aluminum thin film and the like.

[0115] Examples of the inorganic vapor-deposited film include films obtained by vapor-depositing silicon dioxide, aluminum oxide, aluminum, or the like on an adjacent layer.

[0116] The ethylene vinyl alcohol copolymer is a polymer obtained by saponifying an ethylene-vinyl ester copolymer. Among them, an ethylene-vinyl alcohol copolymer having an ethylene content of 5 to 60 mol% and a saponification degree of 85% or more is preferred. The ethylene content of the ethylene vinyl alcohol copolymer is preferably 20 mol% or more, more preferably 25 mol% or more. In addition, it is preferably 55 mol% or less, more preferably 50 mol% or less. The saponification degree of the vinyl ester component is preferably 85% or more, more preferably 90% or more, and further preferably 99% or more.

[0117] Examples of the polyamide resin include aliphatic polyamides and semi-aromatic polyamides, and aliphatic polyamides are preferred from the viewpoint of impact strength.

[0118] Examples of the aliphatic polyamide include nylon 6, nylon 6,6, and nylon 6,12, and nylon 6 and nylon 6,6 are preferred.

[0119] As the semi-aromatic polyamide, a polyamide resin (X) containing a diamine unit including a meta-xylylenediamine unit and a dicarboxylic acid unit including a linear aliphatic dicarboxylic acid unit is preferred.

[0120] The diamine units in the polyamide resin (X) preferably contain 70 mol% or more of meta-xylylenediamine units, more preferably 80 to 100 mol%, and even more preferably 90 to 100 mol%, from the viewpoint of exhibiting excellent gas barrier properties.

[0121] Examples of compounds that can constitute diamine units other than meta-xylylenediamine units include aromatic diamines such as p-xylylenediamine, alicyclic diamines such as 1,3-bis(aminomethyl)cyclohexane and 1,4-bis(aminomethyl)cyclohexane, and linear or branched aliphatic diamines such as tetramethylenediamine, hexamethylenediamine, nonamethylenediamine, and 2-methyl-1,5-pentanediamine. However, the present invention is not limited thereto.

[0122] The dicarboxylic acid units in the polyamide resin (X) preferably contain 70 mol% or more of α,ω-straight-chain aliphatic dicarboxylic acid units having 4 to 20 carbon atoms.

[0123] The content of the C4-20 α,ω-linear aliphatic dicarboxylic acid units in the dicarboxylic acid units is more preferably 85 mol % or more, further preferably 88 mol % or more, further preferably 90 mol % or more, and is 100 mol % or less.

[0124] Furthermore, from the viewpoint of moldability, the dicarboxylic acid unit in the polyamide resin (X) preferably contains an aromatic dicarboxylic acid unit.

[0125] When the dicarboxylic acid unit of the polyamide resin (X) contains an α,ω-straight-chain aliphatic dicarboxylic acid unit having 4 to 20 carbon atoms and an aromatic dicarboxylic acid unit, the content of the α,ω-straight-chain aliphatic dicarboxylic acid unit having 4 to 20 carbon atoms is preferably 85 to 96 mol %, more preferably 88 to 96 mol %, and even more preferably 90 to 94 mol %.

[0126] The content of the aromatic dicarboxylic acid unit is preferably 4 to 15 mol%, more preferably 4 to 12 mol%, and even more preferably 6 to 10 mol%.

[0127] By containing 85 mol% or more of α,ω-straight-chain aliphatic dicarboxylic acid units having 4 to 20 carbon atoms in the dicarboxylic acid units, it is possible to avoid a decrease in gas barrier properties and excessive decrease in crystallinity. In addition, by containing 4 mol% or more of aromatic dicarboxylic acid units, the amorphous property of the polyamide resin (X) increases and the crystallization rate decreases, thereby improving the thermoformability during film forming.

[0128] As compounds capable of constituting α,ω-straight-chain aliphatic dicarboxylic acid units having 4 to 20 carbon atoms, succinic acid, glutaric acid, adipic acid, pimelic acid, suberic acid, azelaic acid, sebacic acid, 1,10-decanedicarboxylic acid, 1,11-undecanedicarboxylic acid, 1,12-dodecanedicarboxylic acid, etc. can be exemplified, but are not limited thereto. They can be used alone or in combination of two or more. Among them, adipic acid is preferred.

[0129] As compounds capable of constituting aromatic dicarboxylic acid units, terephthalic acid, isophthalic acid, 2,6-naphthalenedicarboxylic acid, etc. can be exemplified, but are not limited thereto. They can be used alone or in combination of two or more. Among them, isophthalic acid is preferred from the viewpoints of sublimation properties, ease of acquisition, etc.

[0130] The polyamide resin (X) can be obtained by polycondensing a diamine component containing meta-xylylenediamine and a dicarboxylic acid component containing an α,ω-linear aliphatic dicarboxylic acid having 4 to 20 carbon atoms. During the polycondensation, a small amount of a monoamine or a monocarboxylic acid may be added as a molecular weight modifier.

[0131] The polyamide resin (X) is preferably manufactured by polycondensation by melt polymerization and then solid phase polymerization. As a melt polycondensation method, for example, a method of heating a nylon salt containing a diamine component and a dicarboxylic acid component in the presence of water and under pressure, and polymerizing in a molten state while removing the added water and condensation water can be cited. In addition, a method of directly adding a diamine component to a dicarboxylic acid component in a molten state and performing polycondensation can be cited. At this time, in order to keep the reaction system in a uniform liquid state, the diamine component is continuously added to the dicarboxylic acid component, and the reaction system is heated and polycondensed in a manner that the reaction temperature is not lower than the melting point of the generated oligoamide and polyamide resin.

[0132] Solid phase polymerization is preferably performed after the polymer obtained by melt polycondensation is temporarily taken out. As a heating device used in solid phase polymerization, an intermittent heating device with excellent airtightness and capable of highly isolating the contact between oxygen and the polyamide resin is preferably used compared to a continuous heating device. In particular, a rotary drum type heating device called a drum dryer, a conical dryer, a rotary dryer, etc. and a conical heating device with rotary blades inside called a Nauta mixer are preferably used, but are not limited to these.

[0133] The solid phase polymerization process of polyamide resin is preferably carried out in a manner that polyamide resin pellets are not hot-adherent to each other, or polyamide resin pellets are not attached to the inner wall of the device, by a first process to improve the crystallinity of polyamide resin, a second process to improve the molecular weight of polyamide resin, and a third process of cooling the polyamide resin after solid phase polymerization until the desired molecular weight. The first process is preferably carried out below the glass transition temperature of polyamide resin. The second process is preferably carried out under reduced pressure, at a temperature lower than the melting point of polyamide resin, but is not limited thereto.

[0134] When the gas barrier layer is formed of a gas barrier resin, it may contain any additives such as a lubricant, a matting agent, a heat stabilizer, a weather stabilizer, a UV absorber, a crystallization nucleating agent, a plasticizer, a flame retardant, an antistatic agent, a coloring inhibitor, and a gelation inhibitor within a range that does not impair the effects of the present invention.

[0135] The thickness of the gas barrier layer varies depending on the material of the composition. In the case of an inorganic vapor-deposited film, the thickness is preferably 1 to 1000 nm, more preferably 5 to 500 nm, and further preferably 10 to 300 nm. In the case of containing at least one selected from ethylene vinyl alcohol copolymer and polyamide resin, the thickness is preferably 2 to 100 μm, more preferably 5 to 50 μm, further preferably 10 to 40 μm, and further preferably 15 to 30 μm.

[0136] The gas barrier layer may be formed of one material or a plurality of materials. When formed of a plurality of materials, they may be stacked for use. By stacking and using, a higher barrier effect can be exerted.

[0137] <Protective layer>

[0138] The oxygen-absorbing multilayer film of the present invention preferably has a protective layer in order to protect the gas barrier layer and the oxygen-absorbing layer and improve the design properties.

[0139] The protective layer preferably contains a thermoplastic resin as a main component. Examples include polyolefins such as polyethylene, polypropylene, polybutene, polybutadiene, polymethylpentene, ethylene-propylene copolymer, propylene-ethylene block copolymer; polyolefin copolymers such as ethylene-vinyl acetate copolymer, ethylene-acrylic acid copolymer, ethylene-acrylate copolymer, ethylene-methacrylic acid copolymer, ethylene-methacrylate copolymer; graft polymers of the aforementioned polyolefins or the aforementioned polyolefin copolymers and silicone resins; polyesters such as polyethylene terephthalate; polyamides such as nylon 6 and nylon 6,6; ionomers; elastomers, etc. They can be used alone or in combination of two or more. Among them, it is preferably at least one selected from the group consisting of polypropylene resin, polyamide resin and polyester resin, preferably at least one selected from the group consisting of polypropylene resin and polyester resin, and more preferably polyester resin.

[0140] The thickness of the protective layer is not particularly limited, and varies depending on the layer structure of the multilayer film, but is preferably 2 to 100 μm, more preferably 5 to 50 μm, further preferably 10 to 30 μm, further preferably 10 to 20 μm.

[0141] <Other layers>

[0142] The oxygen-absorbing multilayer film of the present invention may have other layers in addition to the layer mainly composed of polyolefin, the oxygen-absorbing layer, the gas barrier layer, and the optional protective layer, such as adhesive layers and printed layers.

[0143] The adhesive layer is an optional layer, and is preferably provided in order to bond the above-mentioned layers with sufficient strength.

[0144] The adhesive layer contains an adhesive resin as a main component.

[0145] As the adhesive resin, there is no particular limitation, and known adhesive thermoplastic resins can be used. For example, acid-modified polyolefins obtained by modifying olefin resins with unsaturated carboxylic acids such as acrylic acid, methacrylic acid, maleic acid, and maleic anhydride can be cited. These can be used alone or in combination of two or more. As the adhesive resin, from the viewpoint of adhesiveness, it is preferred that the same resin as the polyolefin constituting each layer of the oxygen-absorbing multilayer film of the present invention be modified with unsaturated carboxylic acids to form an acid-modified polyolefin.

[0146] The printed layer is an optional layer, and is preferably provided in order to improve the design of the oxygen-absorbing multilayer film of the present invention and to maintain a good appearance even after absorbing oxygen. The oxygen-absorbing resin composition constituting the oxygen-absorbing layer of the oxygen-absorbing multilayer film of the present invention has excellent light-shielding properties, so the printed layer is preferably provided outside the oxygen-absorbing layer.

[0147] When providing the printing layer, the conventional printing equipment and methods used for printing on polymer films such as gravure printing presses, flexographic printing presses, offset printing presses, etc. can be applied. In addition, as the ink forming the printing layer, the conventional ink composition used for printing on polymer films formed of azo pigments, phthalocyanine pigments, etc., rosin, polyamide resins, polyurethane resins, etc., and solvents such as methanol, ethyl acetate, methyl ethyl ketone, etc. can also be applied.

[0148] Before printing, it is preferred that the surface in contact with the printed layer be subjected to a surface treatment such as flame treatment or corona discharge treatment so as to form a printed layer without unevenness.

[0149] <Applications of oxygen-absorbing multilayer films>

[0150] Since the oxygen-absorbing multilayer film of the present invention contains the oxygen-absorbing film as an oxygen-absorbing layer, it is excellent in oxygen absorbing property, light-shielding property and odor-suppressing performance, and is therefore suitable for packaging containers.

[0151] The packaging container using the oxygen-absorbing multilayer film of the present invention is excellent in oxygen absorbing property and also excellent in light shielding property and odor suppressing performance, and therefore is suitable for packaging of various articles, and in particular, is suitable for packaging of foods.

[0152] Examples of the objects to be stored in the packaging container using the oxygen-absorbing multilayer film of the present invention include beverages such as milk, dairy products, fruit juice, coffee, tea, and alcoholic beverages; liquid seasonings such as sauce, soy sauce, and dressing, soups, stews, curry, cooked foods for infants and nursing care, and other cooked foods; paste-like foods such as jam, mayonnaise, ketchup, and jelly; aquatic products such as tuna, fish, and shellfish; dairy processed products such as cheese and butter; processed livestock meat products such as meat, salami, sausage, and ham; vegetables such as carrots and potatoes; eggs; noodles; rice before cooking, cooked rice, rice porridge, and other processed rice products; powdered seasonings, powdered coffee, powdered milk for infants and infants, powdered diet foods, dried vegetables, pancakes, and other dry foods; and the like.

[0153] Examples of suitable packaging containers for the oxygen-absorbing multilayer film of the present invention include pouches, lids, and laminated tubes. Among these, pouches and lids are preferred, and lids are more preferred.

[0154] [Cover material]

[0155] The covering material of the present invention includes the oxygen-absorbing multilayer film.

[0156] The oxygen-absorbing multilayer film is excellent in oxygen absorbing property and also excellent in light shielding property and odor suppressing performance, and therefore is particularly suitable as a cover material for food containers.

[0157] The layer structure of the cover body used in the present invention is not particularly limited if it is composed of a combination of the layers described in the aforementioned oxygen-absorbing multilayer film. If recorded in order from the outermost layer to the innermost layer, it is preferably a layer structure of protective layer / printed layer / gas barrier layer / oxygen absorbing layer / polyethylene layer, and more preferably a layer structure of protective layer (polyester) / printed layer / gas barrier layer (nylon) / oxygen absorbing layer / polyethylene layer, or a layer structure of protective layer (polyamide) / printed layer / gas barrier layer (nylon) / oxygen absorbing layer / polyethylene layer.

[0158] Examples of the items to be stored in a food container that includes a cover material comprising the oxygen-absorbing multilayer film of the present invention as a part thereof include beverages such as milk, dairy products, fruit juice, coffee, tea, and alcoholic beverages; liquid seasonings such as sauce, soy sauce, and dressing, soups, stews, curry, cooked foods for infants and nursing care, and other cooked foods; paste-like foods such as jam, mayonnaise, ketchup, and jelly; aquatic products such as tuna, fish, and shellfish; dairy processed products such as cheese and butter; processed livestock meat products such as meat, bacon, sausage, and ham; vegetables such as carrots and potatoes; eggs; noodles; rice before cooking, cooked rice, rice porridge, and other processed rice products; powdered seasonings, powdered coffee, powdered milk for infants and infants, powdered diet foods, dried vegetables, pancakes, and other dry foods; and the like.

[0159] Among them, when cooked rice is used as the storage object of the container using the cover material of the present invention, the odor can be suppressed even when cooking and heating, and the cover material has oxygen absorption and light shielding properties, so the taste and flavor of the cooked rice can be significantly improved compared with the container using the conventional cover material.

[0160] Example

[0161] The present invention will be described in more detail below with reference to examples, but the present invention is not limited to these examples.

[0162] <Evaluation Method>

[0163] (1) Oxygen uptake

[0164] The films obtained in Examples and Comparative Examples were cut into pieces having a size of 63 mm×76 mm×140 μm to prepare test pieces.

[0165] The test piece and 500 mL of air were added to the barrier bag and placed at 25°C for 7 days. The gas in the barrier bag was then collected using a syringe, and the oxygen concentration (%) was measured using an oxygen concentration analyzer (manufactured by Dansensor, trade name "CheckMate2"). The oxygen absorption amount (mL) was calculated from the oxygen concentration. The larger the value of the oxygen absorption amount, the better the oxygen absorption performance.

[0166] (2) Odor suppression performance

[0167] 0.5 g of the film obtained in the examples and comparative examples was cut out, added to a petri dish (85 mm in diameter), covered, heated in an electric oven (600 W, 20 seconds), and the lid was immediately opened to evaluate the odor. The odor suppression performance was evaluated on a 4-level scale (1 to 4) using the following criteria. The larger the value, the more the odor was suppressed, the less the odor, and the better the odor suppression performance.

[0168] 4: Very weak odor. If you take a deep sniff, you will feel uncomfortable.

[0169] 3: Weak odor. You will not notice the odor when you first smell it. If you have noticed the odor beforehand and paid attention to it, you will know it when you smell it.

[0170] 2: Slightly strong odor. Even if it is the first time to smell the odor, it is still noticeable without paying attention.

[0171] 1: Strong odor. If the odor is emitted from food or drink, it is noticeable even if you are not paying attention.

[0172] (3) Total light transmittance

[0173] The total light transmittance (%) of the films obtained in Examples and Comparative Examples was measured using Haze Meter NDH4000 manufactured by Nippon Denshoku Industries Co., Ltd. The smaller the value of the total light transmittance, the better the light shielding property.

[0174] (4) Average particle size and maximum particle size

[0175] The average particle size (D50) of calcium oxide, and the average particle size (D50) and maximum particle size (D90) of iron powder were measured using a laser diffraction particle size distribution measuring instrument "LMS-2000e (trade name)" (manufactured by SEISHIN ENTERPRISE Co., Ltd.), and the average particle size (D50) of the cumulative frequency 50% and the average particle size (D90) of the cumulative frequency 90% in the volume-based particle size distribution were measured, respectively. It should be noted that isopropyl alcohol (IPA) was used as a dispersion medium.

[0176] <Manufacturing of oxygen-absorbing films>

[0177] Example 1

[0178] (Titanium oxide masterbatch)

[0179] PEX199094WhiteAL (Linear low-density polyethylene / titanium oxide (TiO 2 )=40 / 60 (mass ratio), manufactured by TOKYO PRINTING INK MFG.CO.,LTD.)

[0180] (Calcium Oxide Masterbatch)

[0181] 35 parts by mass of linear low-density polyethylene (trade name "KC580S", manufactured by Japan Polyethylene Corporation) and 65 parts by mass of calcium oxide (average particle size 5 μm, manufactured by CALFINE CO., LTD) were melt-kneaded at 200° C. using a twin-screw kneading extruder having two screws with a diameter of 37 mm, and strands were extruded from the extruder head. After cooling, pelletization was performed to obtain a calcium oxide masterbatch.

[0182] (Deoxidizer composition)

[0183] Iron powder (trade name "spongy iron powder", average particle size 30 μm, maximum particle size 55 μm, manufactured by Hoganas Japan K.K.) was added to a vacuum mixing dryer with a heating jacket, and 2 parts by mass of an aqueous calcium chloride solution (calcium chloride: water = 1:1 (mass ratio)) was sprayed on 100 parts by mass of the iron powder at 130°C and under a reduced pressure of 10 mmHg, followed by drying to produce a granular deoxidizer composition in which calcium chloride was attached to the surface of the iron powder.

[0184] (Oxygen absorbing resin masterbatch)

[0185] 20.8 parts by mass of the titanium oxide masterbatch, 15 parts by mass of the calcium oxide masterbatch, 50 parts by mass of the deoxidizer composition, and 14.2 parts by mass of a linear low-density polyethylene (trade name "KC580S", manufactured by Japan Polyethylene Corporation) were melt-kneaded at 200° C. using the above-mentioned twin-screw kneading extruder, and strands were extruded from the extruder head. After cooling, pelletization was performed to obtain an oxygen-absorbing resin masterbatch.

[0186] (Manufacture of oxygen-absorbing film)

[0187] Next, 40 parts by mass of the oxygen-absorbing resin masterbatch and 60 parts by mass of a linear low-density polyethylene (trade name "KC580S", manufactured by Japan Polyethylene Corporation) were dry-blended and pressed at 200°C using a hydraulic press to obtain an oxygen-absorbing film (thickness 140 μm) formed of the oxygen-absorbing resin composition. The oxygen absorption amount, odor suppression performance, and total light transmittance of the obtained oxygen-absorbing film were evaluated. The results are shown in Table 1.

[0188] Examples 2 to 4 and Comparative Examples 1 to 7

[0189] When manufacturing the oxygen-absorbing resin masterbatch in the above-mentioned Example 1, the amounts of titanium oxide masterbatch, calcium oxide masterbatch, and linear low-density polyethylene were adjusted so that the contents of calcium oxide and titanium oxide in the oxygen-absorbing film were as shown in Table 1. In the same manner as in Example 1, an oxygen-absorbing film (each with a thickness of 140 μm) was obtained. The oxygen absorption amount, odor suppression performance, and total light transmittance of the obtained oxygen-absorbing film were evaluated. The results are shown in Table 1. It should be noted that the content of iron powder in Table 1 is recorded as the amount (mass %) of calcium chloride contained.

[0190] [Table 1]

[0191]

[0192] The results in Table 1 show that the oxygen-absorbing film formed from the oxygen-absorbing resin composition of the present invention has a large oxygen absorption amount, excellent oxygen absorbing properties, a low total light transmittance, excellent light-shielding properties, and also excellent odor suppressing performance.

Claims

1. An oxygen-absorbing resin composition comprising polyolefin, iron powder, titanium oxide and calcium oxide, The content of the iron powder in the oxygen-absorbing resin composition is 10 to 50% by mass. The mass ratio of titanium oxide to iron powder, that is, titanium oxide / iron powder, is 0.1 to 0.

5. The mass ratio of calcium oxide to iron powder, that is, calcium oxide / iron powder, is 0.1 to 0.

5. The oxygen absorbing resin composition is obtained by melt-kneading a masterbatch containing the titanium oxide and a resin, a masterbatch containing the calcium oxide and a resin, the iron powder, and a part of the polyolefin to obtain an oxygen absorbing resin masterbatch, and further melt-kneading it with the remaining part of the polyolefin.

2. The oxygen-absorbing resin composition according to claim 1, wherein The mass ratio of titanium oxide to iron powder, that is, titanium oxide / iron powder, is 0.15 to 0.

5.

3. The oxygen-absorbing resin composition according to claim 1 or 2, wherein The mass ratio of calcium oxide to titanium oxide, that is, calcium oxide / titanium oxide, is 0.6 to 1.

5.

4. The oxygen-absorbing resin composition according to claim 1 or 2, wherein The content of titanium oxide in the oxygen-absorbing resin composition is 1 to 15% by mass.

5. The oxygen-absorbing resin composition according to claim 1 or 2, wherein The content of calcium oxide in the oxygen-absorbing resin composition is 1 to 15% by mass. 6 . An oxygen-absorbing film, comprising the oxygen-absorbing resin composition according to claim 1 .

7. An oxygen-absorbing multilayer film comprising the oxygen-absorbing film according to claim 6 as an oxygen-absorbing layer.

8. The oxygen-absorbing multilayer film according to claim 7, which has a multilayer structure in which a layer containing polyolefin as a main component, an oxygen-absorbing layer, and a gas barrier layer are sequentially laminated.

9. The oxygen-absorbing multilayer film according to claim 7 or 8, wherein The thickness of the oxygen absorbing layer is 10 to 200 μm.

10. The oxygen-absorbing multilayer film according to claim 8, wherein The gas barrier layer is a metal thin film, an inorganic vapor-deposited film, or a layer containing at least one selected from ethylene vinyl alcohol copolymer and a polyamide resin.

11. The oxygen-absorbing multilayer film according to claim 9, wherein The gas barrier layer is a metal thin film, an inorganic vapor-deposited film, or a layer containing at least one selected from ethylene vinyl alcohol copolymer and a polyamide resin.

12. The oxygen-absorbing multilayer film according to claim 7 or 8, wherein Titanium oxide is contained only in the oxygen absorbing layer. 13 . A cover material comprising the oxygen-absorbing multilayer film according to claim 7 .

Citation Information

Patent Citations

  • Deoxidative lid material and deoxidative sealing container

    JP2004315035A

  • Oxygen absorber composition, oxygen-absorbing multilayer body, oxygen-absorbing packaging container, and method for storing article

    CN108697972A

  • Oxygen-absorbing resin composition and oxygen-absorbing multi-layered body

    JP2000212450A